An unusual simultaneous occurrence of gastric carcinoma with lymphoid stroma, calcified leiomyoma and ectopic pancreas - Faten Limaiem; Sahir Omrani (Clinical Case Reports, 2022)
Abstract Gastric carcinoma with lymphoid stroma is a rare variant of gastric carcinoma accounting for 1%–7% of gastric carcinomas. Its association with gastric leiomyoma and ectopic pancreas is extremely rare. We herein report an unusual simultaneous occurrence of gastric carcinoma with lymphoid stroma, calcified leiomyoma, and ectopic pancreas.